THE EFFECTIVENESS OF USING PROGRAMMING INSTRUCTIONAL VIDEOS IN ENHANCING UNDERSTANDING OF SIMPLE MATHEMATICAL CONCEPTS AMONG EARLY CHILDHOOD STUDENTS AT LESTARI PRESCHOOL - Niswatun Khasanah; Sulhatul Habibah; Winnuly Winnuly (LP2M IAI Al-Khairat Pamekasan, 2026)
This study analyzes the effectiveness of using block coding–based instructional videos to enhance the understanding of basic mathematical concepts among early childhood learners at KB Lestari. Employing a quantitative experimental approach with a pre-test and post-test control group design, the research integrates findings from national and international literature on coding videos, computational thinking, and the Indonesian Kurikulum Merdeka for early childhood education. Results indicate that the visual-logical animations of Scratch Jr. significantly facilitate the introduction of numbers, basic operations, and patterns through the transfer of skills from coding logic to real-world applications, with urban teachers’ readiness serving as a key driving factor. The discussion confirms the superiority of this approach compared to traditional memorization methods, framed through Paivio’s dual-coding theory, Piaget’s constructivism, and Wing’s computational thinking. The study recommends a hybrid curriculum model for national replication to strengthen digital literacy in Indonesian early childhood education.